Risk factors for Hospital-Acquired Pneumonia in nonventilated adults - Fortaleza,Carlos Magno Castelo Branco (2009)
Although most recent publications focus on Ventilator-associated Pneumonia, Non-Ventilator-associated Hospital-acquired pneumonia (NVHAP) is still worrisome. We studied risk factors for NVHAP among patients admitted to a small teaching hospital. Sixty-six NVHAP case patients and 66 controls admitted to the hospital from November 2005 through November 2006 were enrolled in a case-control study. Variables under investigation included: demographic characteristics, comorbidities, procedures, invasive devices and use of medications (Sedatives, Antacids, Steroids and Antimicrobials). Univariate and multivariable analysis (hierarchical models of logistic regression) were performed. The incidence of NVHAP in our hospital was 0.68% (1.02 per 1,000 patients-day). Results from multivariable analysis identified risk factors for NVHAP: age (Odds Ratio[OR]=1.03, 95% Confidence Interval[CI]=1.01-1.05, p=0.002), use of Antacids (OR=5.29, 95%CI=1.89-4.79, p=0.001) and Central Nervous System disease (OR=3.13, 95%CI=1.24-7.93, p=0.02). Although our findings are coherent with previous reports, the association of Antacids with NVHAP recalls a controversial issue in the physiopathology of Hospital-Acquired Pneumonia, with possible implications for preventive strategies.